Three new species of the segmented spider genus Songthela (Araneae: Mesothelae: Liphistiidae) from Guizhou, China - Yuan, Jiayu; Zhang, Yan; Xu, Xin (Zootaxa, 2026)
Three new species of the primitively segmented spider genus Songthela Ono, 2000 are described from Guizhou, China: S. chunguang sp. nov. (♂♀), S. congjiang sp. nov. (♂♀), and S. jinxing sp. nov. (♂♀). All three species are assigned to the multidentata-group based on morphology of the male palps and female genitalia. Detailed diagnoses, descriptions, photographs and a distribution map are provided. Mitochondrial cytochrome c oxidase subunit I (COI) sequences of the holotypes are also presented to facilitate future identification and molecular studies.